Pelvic Ultrasound for Predicting Endometrial Neoplasia in Premenopausal Abnormal Uterine Bleeding - Jessica Grubman; Delaina Bling; Haania Kakwan; Shubhangi Mehra; April Gorman; Alicia Kiszka; Diego H. Castrillon; Elysia Moschos (Journal of Ultrasound in Medicine, 2026)
Objectives Although ultrasound is the first line imaging modality for abnormal uterine bleeding (AUB), there is a lack of consensus on its predictiveness for premenopausal endometrial pathology. This study aims to determine the predictiveness of pelvic ultrasound for endometrial neoplasia and cancer precursor lesions in premenopausal patients accounting for type of AUB. Methods This is a cross‐sectional study of premenopausal individuals at a safety‐net hospital from 2013 to 2021 with AUB who underwent pelvic ultrasound followed by endometrial sampling within 24 hours. AUB was classified by International Federation of Gynecology and Obstetrics PALM‐COEIN terminology. Endometrial atypical hyperplasia/endometrioid intraepithelial neoplasia and carcinoma comprised neoplasia and disordered proliferative endometrium and hyperplasia without atypia constituted endometrial cancer precursor lesions. Chi‐square, sensitivity, specificity, and positive and negative predictive values compared ultrasound and pathology findings. Odds of pathology type were obtained with logistic regression. Results A total of 3791 patients were included; 23.6% had anovulatory‐type AUB (AUB‐O) alone, 30.5% AUB‐O with another etiology, and 45.9% no AUB‐O. Ultrasound had significant positive and negative predictive value for abnormal histopathology. Several findings, including endometrial thickness (EMT), correlated to histopathology regardless of AUB type. No endometrial hyperplasia or cancer was found with EMT